PENGARUH MOTIVASI, DISIPLIN DAN KOMPENSASI FINANSIAL TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN DAERAH KABUPATEN TOJO UNA-UNA - Zaenong, Zaitun N.K. (Katalogis, 2017)
Officials who are currently devoted to providing the best services to the community are recruited through a series of procedures and deemed to meet certain requirements for obtaining high performance. It is described in various theories that the performance of a person is influenced by several factors such as motivation, discipline in work, and compensation given as a form of appreciation of his/her performance at work. The aims of the study is to analyze simulatneous an dpartial influence of motivation, disiplin, and financial compensation on the performance of officials in The Deaprtment of Local Revenues in Tojo Una-Una District. Data is analyzed with multiple linear regressions analysis. Population comprises of 32 officials who selected as respondents through census method. The result reveals that motivation, disiplin, and financial compensation simultaneously and partially influence the performance of officials in The Deaprtment of Local Revenues in Tojo Una-Una District.